Lycopene minimizes skin toxicity and oxidative stress in patients treated with panitumumab-containing therapy for metastatic colorectal cancer. (August 2021) - Moroni, Mauro; Pirovano, Marco; Brugnatelli, Silvia; Zucca, Martina; Morreale, Marco; Rizzo, Vittoria; Ferrari, Alessandra; Tinelli, Carmine; De Silvestri, Annalisa; Meregalli, Maurizio; Giordano, Monica; Artale, Salvatore; et al.
Graphical abstract: Highlights: Lycopene reduces ≥ G2 skin toxicity frequency in course of panitumumab therapy. Lycopene prolongs time to appearance of ≥ G2 skin toxicity ( p  = 0.0007 logrank test) Lycopene protects tissues from oxidative stress due to panitumumab therapy. Lycopene administration saves antioxidants consumption due to panitumumab therapy. Abstract: Epidermal Growth Factor Receptor (EGFR) inhibition leads to the production of reactive oxygen metabolites causing skin inflammatory reactions. Anti-EGFR therapies are frequently associated with skin toxicities which often cause treatment delay and impairment to patient quality of life. Lycopene is a compound in the carotenoid group with an extreme antioxidant action which accumulates in the skin due to its hydrophobic structure. In a pilot study, we describe lactolycopene effectiveness in reducing skin toxicity and protecting tissues from oxidative stress in patients treated with panitumumab. Despite the limited number of patients, we show an absolute reduction of skin grade 2–3 toxicity in 41% of patients and 46% of panitumumab cumulative cycles in the experimental group versus placebo; lactolycopene administration was able to abolish malondialdehyde (MDA) production, a biomarker used to measure lipid peroxidation in the organism, and replenish antioxidant consumption in the course of anti-EGFR therapy. Trial registration: Clinicaltrials.gov NCT 03, 167, 268 (Pasto trial).